A transfectable Fusagravirus from a Japanese strain of Cryphonectria carpinicola with spherical particles - Das, Subha; Hisano, Sakae; Eusebio-Cope, Ana; Kondo, Hideki; Suzuki, Nobuhiro (MDPI, 2022)
A novel dsRNA virus (Cryphonectria carpinicola fusagravirus 1, CcFGV1), isolated from a Japanese strain (JS13) of Cryphonectria carpinicola, was thoroughly characterized. The biological comparison of a set of isogenic CcFGV1-infected and -free (JS13VF) strains indicated asymptomatic infection by CcFGV1. The sequence analysis showed that the virus has a two open reading frame (ORF) genome of 9.6 kbp with the RNA-directed RNA polymerase domain encoded by ORF2. The N-terminal sequencing and peptide mass fingerprinting showed an N-terminally processed or degraded product (150 kDa) of the 5′-proximal ORF1-encoded protein (1462 amino acids) to make up the CcFGV1 spherical particles of ~40 nm in diameter. Interestingly, a portion of CcFGV1 dsRNA co-fractionated with a host protein of 70 kDa. The purified CcFGV1 particles were used to transfect protoplasts of JS13VF as well as the standard strain of an experimental model filamentous fungal host Cryphonectria parasitica. CcFGV1 was confirmed to be associated with asymptomatic infection of both fungi. RNA silencing was shown to target the virus in C. parasitica, resulting in reduced CcFGV1 accumulation by comparing the CcFGV1 content between RNA silencing-competent and -deficient strains. These results indicate the transfectability of spherical particles of a fusagravirus associated with asymptomatic infection.